CRUSTAL STRUCTURE IN SEISMIC AND ASEISMIC REGIONS BASED ON GEOTRAVERSE DATA: BAZALT, RUBIN, KVARTS, AND ARMASH-AKHALTSIKHE GEOTRAVERSES - Popova O.G.; Konovalov Y.F.; Solodilov L.N.; Popov M.G. (My University, 1999)
An analysis of deep crustal structure and seismicity was performed along four traverses (Bazalt, Rubin, Kvarts, and Armash-Akhaltsikhe), which cut across seismic areas, to detect differences in crustal structure between geologic features exhibiting differing degrees of seismic activity. The original information included estimates of V(P), V(S), γ = V(P)/V(S), and the geometry of crustal blocks derived from interpretations of materials furnished by deep explosion seismic and earthquake-generated exchange-wave profiles processed at the GEON Center. The software of the GEO data processing system was used [3], [4]. A set of patterns was found to recognize areas of possible damaging earthquakes; this can be the starting point for further studies in these areas, for deployment of local seismographic networks, and for geophysical monitoring for the purpose of short-term and intermediate-term earthquake prediction.